2020
DOI: 10.1097/sga.0000000000000418
|View full text |Cite
|
Sign up to set email alerts
|

Experiences With Traditional Chinese Medicine Among Patients With Inflammatory Bowel Disease

Abstract: Despite the increasing number of inflammatory bowel disease (IBD) patients using traditional Chinese medicine (TCM), relatively few studies have examined their experiences with TCM in the Chinese healthcare context. The aim of this study was to explore these experiences from the perspective of IBD patients. Adopting a qualitative descriptive method, IBD patients from several comprehensive hospitals in Hangzhou, Zhejiang were recruited through purposive sampling. Data were collected using semistructured intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Interestingly, Chinese patients with Crohn's disease were willing to use TCM for treatment, especially when biological agents failed. Cai et al used semistructured interviews with 14 IBD patients using TCM and explored their reasons and experience of decision-making [ 30 ]. The results showed that patients initiated TCM treatment due to the unsatisfactory effects of other therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Chinese patients with Crohn's disease were willing to use TCM for treatment, especially when biological agents failed. Cai et al used semistructured interviews with 14 IBD patients using TCM and explored their reasons and experience of decision-making [ 30 ]. The results showed that patients initiated TCM treatment due to the unsatisfactory effects of other therapies.…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] However, TCM has a better advantage in the therapy of IBD, which is characterized by multipathways, multilevels, multitargets, and can maintain the medication treatment for a long time with fewer side effects. [27][28][29] Therefore, it is of utmost importance to seek to develop drugs with fewer side effects and significant efficacy than traditional Chinese or natural medicines.…”
Section: Akba Alleviates Dss-induced Inflammatory Injury In Ibd Mice ...mentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) is an important part of the world's traditional medicine, which has many varieties and complex compositions [1][2][3]. The active ingredients of Chinese medicines are the primary elements of their effectiveness and play a crucial role in the treatment of diseases.…”
Section: Introductionmentioning
confidence: 99%